2019
DOI: 10.1097/md.0000000000014310
|View full text |Cite
|
Sign up to set email alerts
|

Solitary renal metastasis from squamous cell carcinoma of the lung

Abstract: Rationale: Non-small cell cancer with isolated unilateral renal metastasis is rare, and the role of radical nephrectomy has not been determined. In the present study, a case of a patient with solitary kidney metastasis from squamous cell lung cancer who underwent radical nephrectomy is reported. Patient concerns: A 74-year-old patient diagnosed with pulmonary squamous cell lung cancer who had undergone radical pulmonary lobectomy and mediastinal lymph node dissection re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Patients with tumor spread to the kidneys are usually asymptomatic, being diagnosed incidentally on imaging. Rarely, they may present with gross hematuria, dull abdominal, or back pain or early satiety [3,10]. Diagnosis of renal metastasis is usually by imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with tumor spread to the kidneys are usually asymptomatic, being diagnosed incidentally on imaging. Rarely, they may present with gross hematuria, dull abdominal, or back pain or early satiety [3,10]. Diagnosis of renal metastasis is usually by imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous occurrence of primary lung cancers with different histology is uncommon, seen in up to only 0.5% of patients with lung cancer [1-2]. Non-small cell lung cancer (NSCLC) constitutes 80% of all lung cancers, and squamous cell carcinoma (SCC) accounts for 40% of these [3]. SCC remains the most common type of lung malignancy seen in any combination of synchronous lung tumors [1].…”
Section: Introductionmentioning
confidence: 99%
“…The aspartate aminotransferase procedure was evaluated using a bichromatic (340-700 nm) rate method, which is a modification of the technique established by the International Federation of Clinical Chemistry (IFCC) [38].…”
Section: Aspartate Aminotransferase (Ast)mentioning
confidence: 99%
“…Verma et al reported 4 cases of solitary kidney metastasis in individuals with pulmonary malignancy that experienced stereotactic body radiation therapy (SBRT) and concluded that SBRT for mitigation of renal metastases from NSCLC is a safe and effective treatment (65). Nephrectomy may also be a beneficial choice in the treatment of solitary kidney metastasis in individuals with NSCLC (66). In this regard, Adamy et al examined the effect of nephrectomy in patients with solitary renal metastatic tumors and suggested that surgical resection may be an appropriate approach with a positive effect on the patients' survival rate (67).…”
Section: Treatment Of Renal Metastasismentioning
confidence: 99%